(untitled) (Papeles, 2025)
Universities have a crucial role in the formation of a socially responsible citizenship and must expand their outcomes furthermore than the production of knowledge, integrating in their theoretical and practical curricula aspects of University Social Responsibility (USR) and Sustainability. The purpose of this study was to analyze the outcomes of a workshop concerning Social Responsibility in university students entering work internships. The sample was integrated by 18 participants form different socioeconomic faculties in a University in Querétaro, Mexico. The workshop was developed using Microlearning as a didactic strategy via Meet platform with a duration of 10 hours divided in 3 sessions, with contents concerning (USR). A pretest and a posttest was applied using a questionnaire with open and option questions to analyze the impact of the workshop as well as a semi guided interview. The results provided by both instruments before and after the workshop showed an increase in the complexity of the responses an indication of the participants of the importance of obtaining this type of information before being placed in work environments, showing therefore the importance of introducing (USR) using didactic strategies as Microlearning in university contexts.